Impact of Ambulatory Care Pharmacist-Led Management on Hemoglobin A1c Values among Patients with Uncontrolled Diabetes in a Primary Care Clinic vs Usual Care over Two Years - Insaf Mohammad; Alyssa Poyer; Roukia Hamoud; Julie George (University of Minnesota Libraries Publishing, 2023)
Background: Literature has shown the positive impact of ambulatory care pharmacists on diabetes management, yet additional research on clinical outcomes compared to traditional care models is warranted.  Objective: The objective of this study is to evaluate the impact of an ambulatory care pharmacist on glycemic control over two years compared to patients who received usual care.  Methods: This retrospective cohort study matched patients with a baseline hemoglobin A1c (HgbA1c) ≥8% managed by the ambulatory care pharmacist to patients who received usual care. The primary outcome was the mean change in HgbA1c over two years. The secondary outcomes were to evaluate the difference in (1) the proportion of patients achieving HgbA1c <8%, (2) the proportion of patients achieving blood pressure <130/80 mmHg, (3) mean LDL, (4) the proportion of patients prescribed SGLT2 inhibitors, GLP-1RA, and sulfonylureas, and (5) severe hypoglycemia after two years.  Results: Data for 180 patients was analyzed over two years. The mean HgbA1c was 10% at baseline vs 8.2% after two years (adjusted mean change -1.92) among pharmacist-managed patients, compared to 9.9% vs 9% respectively for usual care patients (adjusted mean change -0.98) (p=0.004). Among pharmacist-managed patients, 53.5% achieved HgbA1c <8% compared with 34.2% of usual care patients (p=0.014). There were no statistically significant differences in proportion of patients at goal blood pressure, mean LDL, or hypoglycemia between the two groups. After two years, 18.3% of pharmacist-managed and 5.8% of usual care patients were on an SGLT2 inhibitor (p=0.008), and 46.7% of pharmacist-managed and 9.2% of usual care patients were on a GLP-1RA (p<0.001). No difference was found in sulfonylurea utilization.  Conclusion: Patients with HgbA1c >8% managed by an ambulatory care pharmacist had twice the HgbA1c reduction and significantly more utilization of GLP-1RA and SGLT2 inhibitors as compared to controls provided usual care.